Kankanaey domestic architecture as manifestation of acculturative response to American mission in Sagada, Mountain Province - Ealdama, Anna Christina (2012)
This paper highlights on the evolution of houses in Sagada, Mountain Province since the turn of the 20th century: from the oldest extant pre-colonial houses to the most dominant but overlooked GI-clad wooden house. Other identified house types are presented as part of understanding the evolution of its built forms. The objective of the study is to present the significance of cultural response in vernacular house-building and to recognize the importance of the distinct practice of such modern vernacular tradition in the Mountain Province.
Keywords: House construction -- Sagada (Mountain Province); House construction -- Beliefs and practices; House construction -- Sagada (Mountain Province) -- Social life and customs